DIVERSITY OF MOLLUSC COMMUNITIES IN THE SEAGRASS BED IN PULAU GAZUMBO, PENANG, MALAYSIA - Shau Hwai, Aileen Tan; Bt. Abdul Karim, Nur-najmi Basyeer; Yasin, Zulfigar (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
A study on the diversity of mollusc communities inhabiting the seagrass bed of Pulau Gazumbo, Penang, which is known as a manmade island covered with seagrass communities in Malaysia, was conducted. The seagrass species reported in this island are Halophila ovalis Hook (1858), H. ovata Gaud (1827), H. spinulosa Aschers (1875) and H. beccarii den Hartog (1977), with H. ovalis being the dominant species. A total of 15 random lmx lm quadrates were taken on the seagrass bed around the island during lowest tide. A total of 14 species from 12 genera and 9 families of gastropods and a total of 8 species from 8 genera and 6 families of bivalves were reported in this study. Nassarius livescens from the Family Nassariidae is the most dominant molluscs (18 individuals per m2) inhabiting the seagrass beds.